Depression in Ankylosing Spondylitis Patients: An Analysis of Its Occurrence (Journal of Chittagong Medical College Teachers' Association, 2025)
Background: Depressive symptoms or depressive disorders have been reported to be more frequent in chronic inflammatory disorders. However, depression in Ankylosing Spondylitis (AS) was not well studied in our setting, where many patients with AS are attending for management. The study aimed to determine depression among the patients of AS.Materials and methods: Thirty-two AS patients who fulfilled the American Society of Ankylosing Spondylitis criteria were included in this cross-sectional study. Depression was measured by a 5-point Likert scale, developed according to the cultural context of Bangladesh,  and disease activity was measured by the Bath Ankylosing  Spondylitis Disease Activity Index (BASDAI) scale.Results: The mean age of the patients was 36.56 (±12.02)  years with a male-to-female ratio of 7:1. Mean disease duration was 7.5 (±7.67) years. Eighteen (56.3%) patients had depression (2 (11.1%), 7 (38.9%), 5 (27.8%) and 4 (22.2%) patients, respectively, had a minimal, mild, moderate, and severe form of depression. Depression score had a significant positive correlation with BASDAI score (r=0.566, p